Financial Sector Reforms in Algeria, Morocco, and Tunisia : A Preliminary Assessment - Jbili, Abdelali (IMF Working Papers; Working Paper ;, 1997)
This paper reviews and assesses the financial sector reforms in Algeria, Morocco and Tunisia. After a description of the financial sector before reforms, it explains the main features of the comprehensive reform process in each country. It also reviews the sequencing of reforms and discusses econometric evidence of the impact of the reforms on saving in each of the three countries. Subsequently, the paper sets out remaining issues to be addressed in the three countries, including a further strengthening of the banking system and development of financial instruments and markets.